SIMPLE TECHNIQUE FOR MEASURING DOPING EFFECTS ON DISLOCATION MOTION IN SILICON. - Roberts, S; Pirouz, P; Hirsch, P (1983)
A microindentation-based technique has been developed to investigate the influence of doping on dislocation motion in semiconductors and insulators. It allows investigation of the doping effect using simple equipment and small, easily-prepared, specimens. The technique involves high temperature indentation using a standard microhardness tester equipped with a hot-stage, followed by controlled annealing and etching to reveal the dislocation arrays ('rosettes') around indentations. The size of the rosette is indicative of the ease of dislocation motion in the material. A model of dislocation interactions within the residual indentation stress field has been developed; the model allows the evaluation of a critical minimum stress for dislocation motion. Preliminary results on silicon specimens at 400 degree C have shown that rosette sizes are smallest for intrinsic silicon, and increase with increasing doping, with n-dopants being more effective than p-dopants.